Decreasing educational differences in mortality over 40 years: evidence from the Turin Longitudinal Study (Italy). Issue 12 (16th July 2015) - Stringhini, Silvia; Spadea, Teresa; Stroscia, Morena; Onorati, Roberta; Demaria, Moreno; Zengarini, Nicolás; Costa, Giuseppe
Abstract : Background: Recent studies suggest that inequalities in premature mortality have continued to rise over the last decade in most European countries, but not in southern European countries. Methods: In this study, we assess long-term trends (1971–2011) in absolute and relative educational inequalities in all-cause and cause-specific mortality in the Turin Longitudinal Study (Turin, Italy), a record-linkage study including all individuals resident in Turin in the 1971, 1981, 1991 and 2001 censuses, and aged 30–99 years (more than 2 million people). We examined mortality for all causes, cardiovascular disease (CVD), all cancers and specific cancers (lung, breast), as well as smoking and alcohol-related mortality. Results: Overall mortality substantially decreased in all educational groups over the study period, although cancer rates only slightly declined. Absolute inequalities decreased for both genders (SII=962/694 in men/women in 1972–1976 and SII=531/259 in 2007–2011, p<0.01). Among men, absolute inequalities for CVD and alcohol-related causes declined (p<0.05), while remaining stable for other causes of death. Among women, declines in absolute inequalities were observed for CVD, smoking and alcohol-related causes and lung cancer (p<0.05). Relative inequalities in all-cause mortality remained stable for men and decreased for women (RII=1.92/2.03 in men/women in 1972–1976 and RII=2.15/1.32 in 2007–2011). Among men, relative inequalities increased for smoking-related causes, while among women they decreased for all cancers, CVD, smoking-related causes and lung cancer (p<0.05). Conclusions: Absolute inequalities in mortality strongly declined over the study period in both genders. Relative educational inequalities in mortality were generally stable among men; while they tended to narrow among women. In general, this study supports the hypothesis that educational inequalities in mortality have decreased in southern European countries.